Surface engineered mesoporous silica carriers for the controlled delivery of anticancer drug 5-fluorouracil: Computational approach for the drug-carrier interactions using density functional theory - Rehman, Fozia; Khan, Asif Jamal; Sama, Zaib Us; Alobaid, Hussah M.; Gilani, Mazhar Amjad; Safi, Sher Zaman; Muhammad, Nawshad; Rahim, Abdur; Ali, Abid; Guo, Jiahua; Arshad, Muhammad; Emran, Talha Bin (Frontiers in Pharmacology, 2023)
Drug delivery systems are the topmost priority to increase drug safety and efficacy. Hybrid porous silicates SBA-15 and its derivatives SBA@N and SBA@3N were synthesized and loaded with an anticancer drug, 5-Fluorouracil. The drug release was studied in a simulated physiological environment. These materials were characterized by NMR, FTIR, and SEM, small-angle X-ray diffraction, and nitrogen adsorption/desorption techniques. The surface electrostatics of the materials were measured by zeta potential. The drug loading efficiency of the prepared hybrid materials was about 10%. In-vitro drug release profiles were obtained in simulated fluids. Slow drug release kinetics was observed for SBA@3N, which released 7.5% of the entrapped drug in simulated intestinal fluid (SIF, pH 7.2) and 33% in simulated body fluid (SBF, pH 7.2) for 72 hours, respectively. The material, SBA@N presented an initial burst release of 13% in simulated intestinal fluid and 32.6% in simulated gastric fluid (SGF, pH 1.2), while about 70% of the drug was released within 72 hours. DFT calculations have also supported the slow drug release from the SBA@3N material. The release mechanism of the drug from the prepared carriers was studied by First-order, Second-order, Korsmeyer Peppas, Hixson–Crowell, and Higuchi kinetic models. The drug release from these carriers follows Fickian diffusion and zero-order kinetics in SGF and SBF, whereas First-order, non-Fickian diffusion, and case-II transport were observed in SIF. Based on these findings, the proposed synthesized hybrid materials may be suggested as a potential drug delivery system for anti-cancer drugs such as 5-Fluorouracil.